N00BS NEED NOT APPLY: WiiWARE, GENERATIVITY, AND INDIE GAME DESIGNERS - Plothe, Theo (AoIR Selected Papers of Internet Research, 2014)
The Nintendo Wii represented a shift in video game consoles not only from a static to motion controller, but also in presenting a console as a web portal. Connected to the Internet, it allowed consumers to buy other games using its WiiWare interface. For indie game developers, the interface opened a new digital distribution system. I analyze Nintendo’s developer authorization forms which outline the guidelines and approval process, discuss game approvals and rejections based on their content, and outline the consequences of Nintendo’s developer authorization process for developers’ and consumers’ freedom of expression and consumption. I argue that Nintendo’s Authorized Developer Application violates the generativity principle, significantly restricting the market for developers as well as for consumers.